Does Mothers’ Self-Construal Contribute to Parenting Beyond Socioeconomic Status and Maternal Efficacy? an Exploratory Study of Turkish Mothers - Corapci, Feyza; Benveniste, Hande; Bilge, Sibel (Frontiers in Psychology, 2018)
This study examined the relative contribution of mothers’ self-construal to parenting above and beyond family socioeconomic status (SES) and maternal efficacy beliefs about parenting. A total of 58 Turkish mothers and their preschool-aged children participated in dyadic tasks in the laboratory setting. For the measurement of parenting, direct behavioral observations of mother-child interactions in three interaction contexts were utilized, and mother ratings of emotion socialization were obtained. Mothers also reported on their parenting efficacy, self-construal, child temperament, and family demographics. Results revealed a more balanced endorsement of autonomous and relational self characteristics as well as more sensitive parenting among higher SES mothers. Furthermore, mothers’ self-construal contributed unique variance to the prediction of sensitive parenting over and above SES, maternal efficacy and child temperament. Yet, in the prediction of negatively controlling parenting, mothers’ self-construal did not account for unique variance. Lower parenting efficacy and lower SES were the only predictors of punishing, overriding, and distress magnifying responses. Finally, results indicated a marginally significant indirect effect from SES to sensitive parenting via autonomous-related self-construal, controlling for the indirect effect of maternal efficacy.